EARLY MOBILIZATION AND PAIN MANAGEMENT AS DETERMINANTS OF RECOVERY QUALITY AMONG POSTPARTUM MOTHERS FOLLOWING CESAREAN SECTION AT GATOEL HOSPITAL, MOJOKERTO - Catur Prasastia lukita Dewi (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
The increasing rate of cesarean section deliveries contributes to a higher risk of postoperative pain and delayed mobilization among postpartum mothers, which may negatively affect both physical and psychological recovery. Inadequately managed pain and limitations in early mobilization can prolong the recovery period, increase the risk of complications, and reduce the quality of life of postpartum mothers. This study aimed to analyze the correlation between the implementation of early mobilization and pain management and the quality of recovery among postpartum mothers following cesarean section. This study employed a quantitative approach using an observational analytic design with a cross-sectional method. The study subjects were postpartum mothers following cesarean section who were hospitalized at Gatoel Hospital, Mojokerto. Data were collected using standardized instruments to assess pain intensity (Numeric Rating Scale), implementation of early mobilization, and maternal recovery quality. Data analysis was performed using bivariate analysis (Chi-Square test) and multivariate analysis (Ordinal Logistic Regression) to determine the most dominant relationship between early mobilization, pain management, and recovery quality. The results demonstrated a significant relationship between early mobilization and recovery quality (p = 0.001; p < 0.05). Likewise, a significant relationship was found between pain management and recovery quality (p = 0.003; p < 0.05). Ordinal logistic regression analysis revealed that early mobilization was the most dominant factor influencing the quality of recovery among postpartum mothers following cesarean section, with an odds ratio (OR) of 5.21. These findings indicate that early mobilization directly contributes to the restoration of physiological functions and enhances patient independence during the hospitalization period. Early mobilization and pain management are important factors influencing the quality of recovery among postpartum mothers following cesarean section. Early mobilization was identified as the most dominant determinant and should therefore become a primary focus of evidence-based nursing care at Gatoel Hospital, Mojokerto.